Tachycardia-induced cardiomyopathy in a patient with left-sided accessory pathway and left bundle branch block: A case report. Issue 32 (August 2019) - Minciuna, Ioan Alexandru; Puiu, Mihai; Cismaru, Gabriel; Gusetu, Gabriel; Comsa, Horatiu; Caloian, Bogdan; Zdrenghea, Dumitru; Pop, Dana; Radu, Rosu
Abstract: Rationale: Tachycardia-induced cardiomyopathy (TIC) is defined as systolic and/or diastolic dysfunction of the left ventricle resulting from prolonged elevated heart rates, completely reversible upon control of the arrhythmia. Atrioventricular reentrant tachycardia (AVRT) is one of the most frequent causes of TIC. In its incessant form, it is unlikely to be controlled by pharmacological treatment, catheter ablation being the principal therapeutic option. The coexistence of left bundle branch block (LBBB) in patients with AVRT may cause difficulties in the early diagnosis and management of tachycardia because of the wide complex morphology, making it harder to localize the accessory pathway (AP). Patient concerns: A 60-year-old woman, presented incessant episodes of palpitations and shortness of breath due to a LBBB tachycardia leading to hemodynamic instability. Diagnosis: The patient had a wide QRS tachycardia, with LBBB morphology and a heart rate of 160/minute. Echocardiography showed global hypokinesia with 25% left ventricular ejection fraction (LVEF). Considering the patient's clinical picture, TIC was suspected. Interventions: The electrophysiological study revealed a left lateral accessory pathway. Catheter ablation was successfully performed at the level of the lateral mitral ring. Outcomes: One week after the ablation the patient had no signs of heart failure and the LVEF normalized to 55%. During 6-months follow-up the patient presented no more episodes of tachycardia or heart failure and the LVEF remained normal. Lessons: AVRT is rarely associated with intrinsic LBBB, being a potential cause of TIC. In these patients, it is unlikely to control the arrhythmia pharmacologically, catheter ablation being the best therapeutic option. The variation of QRS complex duration between LBBB pattern in SR and AVRT could be useful for early diagnosis of an ipsilateral AP on surface ECG.